Product Market Integration, Comparative Advantages and Labour Market Performance - Torben M. Andersen; Jan Rose Skaksen (Copenhagen Business School (CBS), Department of Economics, 2006)
In this paper, we set up a two-country general equilibrium model where trade unions have wage bargaining power. We show that a decrease in trade distortions inducing further product market integration gives rise to specialization gains as well as a labour market reform effect. The implications of the specialization gains are similar to an increase in labour productivity, whereas the labour market reform effect is similar to an increase in the degree of competition in the labour market. Wages, employment and welfare increase as a result of further product market integration. It is interesting to note that the labour market reform effect of product market integration is achieved despite an increase in the wage level.
hdl:10398/7655
Keywords: F15; J30; J50; 330; Trade frictions; wage formation; employment; welfare